PERILAKU KOMUNIKASI IBU RUMAH TANGGA DALAM MENINGKATKAN PENGETAHUAN KETAHANAN PANGAN: STUDI PADA RUMAH TANGGA NELAYAN DI KOTA BENGKULU - Yuliarso, M. Zulkarnain (Jurnal AGRISEP, 2010)
This research aimed at  identifying the communication behavior of the household wife toward food security’s knowledge.  This communication behaviour includes information searching and transmissionboth its frequency and quality (communication level),gathered from mass media and interpersonal communication.  This study was survey research with 30 people was selected using simple random sampling.  Data analyzed using descriptive qualitative analysis based on frequency tabulation.  Diversification, stabilitation, and food intake  information are  favourable towardsand much communicated by respondents. Communication level ranges from only small talk, interdependent to interactive communication.  Respondents gained their information from PKK and Posyandu cadres, nurse and private doctor, and community healts centre crew.  Mass media were not used as information sources, but it is more likely entertainment media.